2007
DOI: 10.1667/rr0811.1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated DNA Damage Repair by Trichostatin A through BRCA1 Suppression

Abstract: Recent studies have demonstrated that some histone deacetylase (HDAC) inhibitors enhance cellular radiation sensitivity. However, the underlying mechanism for such a radiosensitizing effect remains unexplored. Here we show evidence that treatment with the HDAC inhibitor trichostatin A (TSA) impairs radiation-induced repair of DNA damage. The effect of TSA on the kinetics of DNA damage repair was measured by performing the comet assay and gamma-H2AX focus analysis in radioresistant human squamous carcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 33 publications
3
67
0
2
Order By: Relevance
“…The authors suggest that 17DMAG inhibits the repair of DNA DSBs induced by radiation (Dote et al, 2006), Similarly, an inhibition of homologous DNA recombination repair, that is, degradation of BRCA2 and alteration of Rad51 by 17-AAG, causes the radiosensitisation of prostate carcinoma DU145 and lung squamous carcinoma SQ-5 cell lines (Noguchi et al, 2006). Similar effects on histone gH2AX, for example, prolonged persistence of DNA damage measured by this sensitive marker, have been shown in several studies using HDAC inhibitors that indirectly block Hsp90 by acetylation (Zhang et al, 2007;Zuco et al, 2010). As suggested by a reviewer, we analysed the expression of several DNA repair proteins, including Ku70, Ku80, Rad50, Rad51, DNA-PKcs and BRCA2.…”
Section: Discussionmentioning
confidence: 66%
“…The authors suggest that 17DMAG inhibits the repair of DNA DSBs induced by radiation (Dote et al, 2006), Similarly, an inhibition of homologous DNA recombination repair, that is, degradation of BRCA2 and alteration of Rad51 by 17-AAG, causes the radiosensitisation of prostate carcinoma DU145 and lung squamous carcinoma SQ-5 cell lines (Noguchi et al, 2006). Similar effects on histone gH2AX, for example, prolonged persistence of DNA damage measured by this sensitive marker, have been shown in several studies using HDAC inhibitors that indirectly block Hsp90 by acetylation (Zhang et al, 2007;Zuco et al, 2010). As suggested by a reviewer, we analysed the expression of several DNA repair proteins, including Ku70, Ku80, Rad50, Rad51, DNA-PKcs and BRCA2.…”
Section: Discussionmentioning
confidence: 66%
“…Enhanced DNA damage observed in culture with combined inhibitors has been attributed to induction of histone hyperacetylation by the HDAC inhibitor, resulting in a more open chromatin structure, making DNA more susceptible to damage by various toxic agents (35). Pan-HDAC inhibitors such as SAHA can suppress DNA repair proteins in transformed cells, resulting in failure to repair DNA damage (36)(37)(38). HDAC6 inhibition does not cause accumulation of acetylated histones.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that Ku70 acetylation does not affect the formation of a complex with its natural partner, Ku80; but, when the authors mimicked acetylation by replacing key lysines with glutamines, the ability of Ku70 to bind DNA extremities was suppressed [65]. involved in both DSB sensing and repair) [66]. In this study, TSA did not sensitize BRCA1-null cells to irradiation, whereas a cell line complemented with a BRCA1 wild-type allele showed a TSA-dependent enhanced susceptibility to IR, suggesting that down-regulation of BRCA1 is a key event in HDACI-induced radiosensitization [66].…”
Section: Hdaci and Double Strand Break Repair Machinerymentioning
confidence: 95%
“…involved in both DSB sensing and repair) [66]. In this study, TSA did not sensitize BRCA1-null cells to irradiation, whereas a cell line complemented with a BRCA1 wild-type allele showed a TSA-dependent enhanced susceptibility to IR, suggesting that down-regulation of BRCA1 is a key event in HDACI-induced radiosensitization [66]. However, the picture is likely to be much more complex since this study did not detect a change in gene expression for the key strand transfer protein RAD51, whereas another group found that it was downregulated to one third of its normal levels following treatment with PCI-24781, another broadspectrum HDACI [67].…”
Section: Hdaci and Double Strand Break Repair Machinerymentioning
confidence: 99%